2015
DOI: 10.2106/jbjs.n.01066
|View full text |Cite
|
Sign up to set email alerts
|

In-Home Telerehabilitation Compared with Face-to-Face Rehabilitation After Total Knee Arthroplasty

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
326
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(343 citation statements)
references
References 34 publications
4
326
1
12
Order By: Relevance
“…25,36,46 Acceptance of mobile technology by the elderly was mentioned in the introduction, and it was reinforced in the literature. 23,25,52 The improvement of access included technology to enhance coordination of care without the limitations of proximity or mobility. 40,46,55 The theme of convenient was only mentioned once (2%).…”
Section: Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,36,46 Acceptance of mobile technology by the elderly was mentioned in the introduction, and it was reinforced in the literature. 23,25,52 The improvement of access included technology to enhance coordination of care without the limitations of proximity or mobility. 40,46,55 The theme of convenient was only mentioned once (2%).…”
Section: Facilitatorsmentioning
confidence: 99%
“…24,26,29,[44][45][46]50,51 Due to the cost of technology, this method of delivery of care highlights a digital divide, and it creates a sense of exclusivity and complexity which can create limitations based on the user's abilities. [23][24][25][30][31][32][33]37,39,43,45,46,55 This theme encompassed observations that organisations need additional technical personnel to handle the additional workload associated with this new modality of care.…”
Section: Barriersmentioning
confidence: 99%
“…In the field of telerehabililitation, results from a randomized clinical trial comparing in-person physical therapy to in-home telerehabilitation showed similar outcomes for patients at a cost reduced by 18% (Moffet et al, 2015;Tousignant et al, 2015). Fortney et al (2013) clearly demonstrated the advantages that the telehealth approach has over practice-based collaborative care in the domain of mental health.…”
mentioning
confidence: 96%
“…Telemedicine is a health service in which information is remotely exchanged between a medical specialist and a patient for the awareness, prevention, diagnosis, and treatment of and rehabilitation from diseases using information and communication technologies that promote access to and opportunity to receive services by populations facing limited supply of and/or access to such services in their geographical area (i.e., the geographically vulnerable population) [2,3]. Remote clinical care has been performed in both teleassisted [4][5][6][7] and teleoperated manners [8][9][10][11]. The term "teleassisted" refers to a visual or over-the-phone telemonitoring system by which the therapy processes are specified and that works as a guide for treating of the patient [12].…”
mentioning
confidence: 99%